A reply to Fossen et al. (2020) comment to "Neoproterozoic magmatic arc systems of the central Ribeira belt, SE-Brazil, in the context of the West-Gondwana pre-collisional history: A review". (March 2021) - Heilbron, Monica; de Morisson Valeriano, Claudio; Peixoto, Caroline; Tupinambá, Miguel; Neubauer, Franz; Dussin, Ivo; Corrales, Felipe; Bruno, Henrique; Lobato, Marcela; Horta de Almeida, Julio Cesar; Guilherme do Eirado Silva, Luiz
Abstract: The scope of the original manuscript of Heilbron et al. (2020) was to present a geological, geochemical, isotopic, petrologic and geochronological synthesis regarding the Neoproterozoic (850–530 Ma) Ribeira orogenic belt. The magmatic arc-related associations of this orogenic belt were developed during the amalgamation of West Gondwana and display accretionary and collisional magmatic arc signatures similar to modern orogenic belts worldwide, i.e., Andes, North American Cordillera, Caledonides, Himalayas. The magmatic arc signature of igneous rocks has been intensely debated throughout the last decades, whether in the Archean or in the Paleoproterozoic, but at least since 2.5 Ga there is a growing consensus regarding the worldwide distribution of Phanerozoic-style plate tectonics, including rocks with pre, syn and post-collisional signatures. Our proposed evolutionary model is based not only on geochemistry data, as suggested by the authors of the comment, but on the integration of analytical data with very detailed geological maps produced by institutional research projects from our group of the Rio de Janeiro State University, from the Rio de Janeiro State Geological Survey and from Brazilian Geological Survey. The comment of Fossen et al. (2020) suggests that our work is selective in many ways of discussing data. However, they present a very biased comment, since they did not discuss all published data available in the literature, instead citing mainly their own papers, which do not bring or discuss geochemical data. Fossen et al. (2020) implies in a rather patronizing way that we do not know how to interpret geochemistry diagrams, geochronological data or even metamorphic petrology, which does not stimulate any reasonable scientific debate. In order to address their comments, we present again most of the evidence used to build the comprehensive proposed tectonic model for the Central Ribeira belt. Our reply, indeed, is not only an answer to the loose comments on our contribution, but a statement of firm opposition towards this negativistic crusade against plate tectonic models for the evolution of the Ribeira belt and similar Neoproterozoic belts of Western Gondwana.